Indonesian Marine Natural Product for Anticancer - Sidik, Faizah Zahrah; Mustofa, Syazili; Kurniawaty, Evi; Rohman, Miftahur (Fakultas Kedokteran Universitas Lampung, 2025)
The development of anticancer drugs derived from marine products in Indonesia offers significant promise due to the country’s rich marine biodiversity. Marine organisms such as algae, sponges, and marine microorganisms are a valuable source of bioactive compounds with potential anticancer properties. These compounds, including polysaccharides, alkaloids, and peptides, exhibit the ability to inhibit cancer cell proliferation, induce apoptosis, and overcome drug resistance, presenting innovative solutions for cancer treatment. Key marine species being investigated include Eucheuma sp., Ulva lactuca, Gracilaria verrucosa, Sargassum polycystum, and Ecteinascidia turbinata, all of which show potent cytotoxicity and diverse mechanisms of action. However, challenges such as sustainable harvesting, compound isolation, and clinical testing must be addressed for these marine products to be successfully developed into therapeutic agents. This paper explores the current state of research on Indonesian marine products as anticancer agents, highlighting their bioactive properties and the opportunities and challenges in advancing these products toward clinical application. Keywords: anticancer, extract, Indonesia, marine products, secondary metabolite.